Effect of the Age-Adjusted Charlson Comorbidity Index on All-Cause Mortality and Readmission in Older Surgical Patients: A National Multicenter, Prospective Cohort Study - Zhang, Xiao-Ming; Wu, Xin-Juan; Cao, Jing; Guo, Na; Bo, Hai-Xin; Ma, Yu-Fen; Jiao, Jing; Zhu, Chen (Frontiers in Medicine, 2022)
Background: Identifying a high-risk group of older people before surgical procedures is very important. The study aimed to explore the association between the age-adjusted Charlson comorbidity index (ACCI) and all-cause mortality and readmission among older Chinese surgical patients (age≥65 years). Methods: A large-scale cohort study was performed in 25 general public hospitals from six different geographic regions of China. Trained registered nurses gathered data on clinical and sociodemographic characteristics. All-cause mortality was recorded when patients died during hospitalization or during the 90-day follow-up period. Readmission was also tracked from hospital discharge to the 90-day follow-up. The ACCI, in assessing comorbidities, was categorized into two groups (≥5 versus <5). A multiple regression model was used to examine the association between the ACCI and all-cause mortality and readmission. Results: There were 3911 older surgical patients (mean=72.46, SD=6.22) in our study, with 1934 (49.45%) males. The average ACCI score was 4.77 (SD=1.99), and all-cause mortality was 2.51% (high ACCI=5.06% versus low ACCI=0.66%, P<0.001). After controlling for all potential confounders, the ACCI score was an independent risk factor for 90-day hospital readmission (OR=1.18, 95% CI: 1.14, 1.23) and 90-day all-cause mortality (OR=1.26, 95% CI: 1.16-1.36). Furthermore, older surgical patients with a high ACCI (≥5) had an increased risk of all-cause mortality (OR=6.13, 95% CI: 3.17, 11.85) and readmission (OR=2.13, 95% CI: 1.78, 2.56) compared to those with a low ACCI (<5). The discrimination performance of the ACCI was moderate for mortality (AUC: 0.757, 95% CI: 0.715-0.80; specificity=0.591, sensitivity=0.846) but poor for readmission (AUC: 0.627, 95% CI: 0.605-0.648; specificity=0.620; sensitivity=0.590). Conclusions: The ACCI is an independent risk factor for all-cause mortality and hospital readmission among older Chinese surgical patients and could be a potential risk assessment tool to stratify high-risk older patients for surgical procedures.